Open Journal Systems as a Pedagogical Tool to Teach and Learn Scholarly Publishing: The Helsinki University Library Experience - Koskinen, Kimmo; Roinila, Markku; Syvälahti, Kati (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
Academic libraries play a pivotal role in promoting open science, providing essential services for opening research and education. The library has also a key role in increasing awareness of open educational resources and practices. Editori is an open journal service at the University of Helsinki designed with an educational focus, providing simultaneously a contribution to the rising trend of university-based and library-based publishing. We show how this service, based on Open Journal Systems (OJS), can be applied as a pedagogical tool for teaching scholarly publishing skills to university students. In 2019 Helsinki University Library initiated a pilot project together with the Working Seminar of Doctoral Programme in Philosophy, Arts and Society of the Arts Faculty of the University of Helsinki. We outline expected pedagogical outcomes from the project, relating to scholarly communication skills, report feedback from teachers and students and discuss implications for future service development. In sum, students and teachers found the Editori platform intuitive and easy to use, although the learning curve for course leaders was considered steep in the initial phase.